In-person psychoeducational intervention to reduce rehospitalizations and improve the clinical course of major depressive disorder: a non-randomized pilot study - Breznoscakova, Dagmar; Pallayova, Maria; Izakova, Lubomira; Kralova, Maria (Frontiers in Psychiatry, 2024)
Background Emerging issues in the management of major depressive disorder (MDD) comprise a nonadherence to treatment and treatment failures, depressive recurrence and relapses, misidentification of incoming exacerbated phases and consequently, a chronification of depression. While antidepressant drugs constitute the standard of care for MDD, effective psychosocial interventions are needed to reduce rehospitalizations and other adverse events. The present study primarily investigated the effects and impact of implementing a structured psychoeducational intervention on the clinical course of MDD. Methods A non-randomized comparative, pragmatic, pilot, single-center study of adults with nonpsychotic moderate or severe episode of MDD recently discharged from a psychiatric hospitalization. The consecutive subjects were allocated either to the intervention group (N=49) or to the attention control group (N=47), based on their preference. The psychoeducational intervention was based on a modified Munoz’s Depression Prevention Course. Subjects were followed up prospectively for two years. Results The absolute changes in Beck anxiety inventory scale, Zung’s depression questionnaire, and Montgomery and Äsberg depression rating scale (MADRS) total scores at 6-month follow-up were comparable between the two groups. There were lower rates of the rehospitalization within one year (2.1% vs. 16.7%; P<0.001) and less rehospitalizations after one year (6.3% vs. 25%; P<0.001), lower rates of the ongoing sickness absence (11.5% vs. 29.2%; P<0.001), less persons with disability due to MDD at 1-year follow-up (1% vs. 11.5%; P=0.002), and less nonadherent subjects who self-discontinued treatment (6.3% vs. 28.1%; P<0.001) among participants in the intervention group compared to the control group. The disability due to MDD at 1-year follow-up was predicted by the absence of the psychoeducational intervention (P=0.002) and by the MADRS total score at 6-month follow-up (OR 1.10; 95% CI 1.003–1.195; P=0.044). Qualitative data indicated the intervention was desired and appreciated by the participants, as well as being practical to implement in Slovakian clinical settings. Conclusion The results suggest the psychoeducational intervention based on a modified Munoz’s Depression Prevention Course has beneficial effects in adults with MDD recently discharged from a psychiatric hospitalization. The findings implicate the psychoeducational intervention may offer a new approach to the prevention of depressive relapses.